(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
In this paper, we are publishing a little-known version of Branko Ćopić’s poem “My Little One from Bosanska Krupa”, which is kept in his personal fund in the Archives of the Serbian Academy of Sciences and Arts.